2012
DOI: 10.1007/bf03404441
|View full text |Cite
|
Sign up to set email alerts
|

On-time Vaccination Coverage in Premature Infants in Ontario, 2002–2009

Abstract: remature and low birth weight (LBW) children are at increased risk of complications from vaccine-preventable diseases, including pertussis 1 and pneumococcal infection. 2 Consequently, the Public Health Agency of Canada and the American Academy of Pediatrics both recommend that premature and LBW children, if medically stable, should be vaccinated with the routinely recommended childhood vaccines at the same chronological age as full-term infants (i.e., no delay for degree of prematurity) with the exception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
3
10
1
2
Order By: Relevance
“…A similar association between gestational age and lower rates of vaccination was reported by Wilson et al. () but only in conjunction with the infant being hospitalised. This is in contrast to the finding that hospitalisation meant that infants with a gestational age of <28 weeks were significantly more likely to be up to date at 2 months (Crawford et al., ).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…A similar association between gestational age and lower rates of vaccination was reported by Wilson et al. () but only in conjunction with the infant being hospitalised. This is in contrast to the finding that hospitalisation meant that infants with a gestational age of <28 weeks were significantly more likely to be up to date at 2 months (Crawford et al., ).…”
Section: Resultssupporting
confidence: 83%
“…Two studies observed an overall delay in vaccination uptake in preterm infants, and relative to full-term infants, preterm infants had lower up-to-date statuses (Denizot et al, 2011;Tillmann et al, 2001). A similar association between gestational age and lower rates of vaccination was reported by Wilson et al (2012) but only in conjunction with the infant being hospitalised. This is in contrast to the finding that hospitalisation meant that infants with a gestational age of <28 weeks were significantly more likely to be up to date at 2 months (Crawford et al, 2009).…”
Section: Gestational Age and Birthweightsupporting
confidence: 76%
See 2 more Smart Citations
“…(10,34) However this is not always followed, as showed in a recent study. (35) In the evaluated NICUs the standard practice is to start immunizations after the patient is discharged which could be after 2 months for VLBW infants. This practice also contribute of the delay in immunizations.…”
Section: Discusionmentioning
confidence: 99%